Manajemen Asuhan Kebidanan pada NY.S Masa Nifas Fisiologis 3 Hari Post Partum di PMB BD. Riyanti, STR.KEB Bangetayu Kulon Genuk Kota Semarang Provinsi Jawa Tengah Tahun 2024 - Irma Suryani; Febriana Sari; Riyanti Riyanti; Sonia Novita Sari; Juliana Munthe (STIKES Columbia Asia Medan, 2024)
postpartum period is the period a woman goes through, starting after giving birth to the products of conception (baby and placenta) and ending up to 6 weeks after giving birth. During the postpartum period, the reproductive organs will slowly experience changes to the state before pregnancy. This change in the reproductive organs is called involution. Postpartum care is needed during this period because it is a critical period for both mother and baby. It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum deaths occur within the first 24 hours. Postpartum care is carried out to reduce maternal mortality because the postpartum period is a critical period that needs monitoring. Results: care for NY